Facilitators and barriers to the protection and promotion of the health and safety of older workers. Issue 1 (2nd January 2017) - Drake, Carolyn; Haslam, Roger; Haslam, Cheryl
Abstract: Individuals may experience health issues or physical, sensory or psychological capability changes related to ageing. With the removal of the default retirement age in the UK, older workers can remain in work well into later life. Health and safety statistics, however, indicate that they are a vulnerable group. Older workers have much to contribute, but employers have a responsibility to examine the working environment to protect those with reduced capabilities. This article reviews two qualitative studies examining the facilitators and barriers to implementing age management strategies to promote the health and safety of older workers. The findings reveal that employers are uncertain how to proceed with implementing actions to protect older workers. Discussions with older workers reveal they do not feel supported or engaged. They are fearful of reporting any capability changes that may affect their ability to perform work tasks as they believe this may have negative consequences for their future employment. A co-ordinated multi-disciplinary approach between human resources, operational management, health and safety specialists and occupational health functions is required.